Impact of Microstructure and Polarization on the Degradation of Ni-YSZ Electrode: An Experimental and Modeling Approach. (10th July 2019) - Monaco, Federico; Hubert, Maxime; Vulliet, Julien; Montinaro, Dario; Ouweltjes, Jan Pieter; Cloetens, Peter; Piccardo, Paolo; Lefebvre-Joud, Florence; Laurencin, Jérôme
Abstract : Solid oxide cells with classical Ni-YSZ hydrogen electrodes were operated in fuel cell and electrolysis mode in order to assess the impact of the initial microstructure on the electrochemical and microstructural stability of the cermet. The pristine and aged electrodes have been reconstructed by synchrotron X-ray holotomography. The gradients in microstructural properties have been determined in the vicinity of the electrode/electrolyte interface and in the bulk of the electrodes. Significant Ni depletion was detected only in the electrochemically active region of the aged cells operated in electrolysis mode, while the volatilization is rather limited for the other samples. Besides, substantial Ni agglomeration was confirmed for all aged cermets. The electrode stability was found to depend on the initial electrode microstructure. The microstructural properties have been introduced in multi-scale models to estimate the impact of Ni evolution on the cell performance and to analyze the underlying causes of volatilization and agglomeration.